The Gendered Face of Ageism in the Workplace - McConatha, Jasmin Tahmaseb; Kumar, V. K.; Magnarelli, Jaqueline; Hanna, Georgina (Advances in Social Sciences Research Journal, 2023)
This qualitative study explores perceived age discrimination in the workplace. Increasing age diversity in the workplace has led to an associated increase in ageism. While a large percentage of older workers report being subjected to discriminatory treatment in the workplace, ageism also appears to be gendered. Older female workers are being victimized at a greater rate than their male counterparts. The intersection of age, gender, and other forms of discrimination results in increased stress, threatens the well-being of workers of all ages, and creates a toxic workplace climate. Analysis of 244 participants’ responses to open-ended items indicated that ageism is prevalent in the workplace and threatens work and life satisfaction. In this study, both male and female participants were negatively affected by ageism in the workplace, although the female participants reported experiencing workplace discrimination more frequently. Qualitative analysis identified several important themes relating to ageism; these included threats to feelings of competence; self-doubt and helplessness; being subjected to momism; feeling isolated and lonely; and gradual disengagement from the workplace. The results are discussed in relation to workplace inclusivity and individual, organizational, and societal consequences of age discrimination.